Low sodium diet for gastric cancer prevention in the United States: Results of a Markov model. (1st December 2020) - Kim, Judith; Oh, Aaron; Truong, Han; Laszkowska, Monika; Camargo, M. Constanza; Abrams, Julian; Hur, Chin
Abstract: Background and Aims: High sodium consumption has been associated with an increased risk of gastric cancer. The mean daily sodium intake in the United States substantially exceeds the national recommended amount. The low sodium‐DASH diet has been shown to decrease the risk of cardiovascular disease in the United States, but its impact on gastric cancer has not been well studied. We therefore aimed to model the impact and cost‐effectiveness of the low sodium‐DASH diet for gastric cancer prevention in the U.S. population. Methods: A Markov cohort state‐transition model was developed to simulate the impact of the low sodium‐DASH diet on gastric cancer outcomes for the average 40‐year‐old in the United States compared to no intervention. Primary outcomes of interest were gastric cancer incidence and incremental cost‐effectiveness ratios (ICER). Results: Our model found that compared to the no intervention cohort, the risk of gastric cancer decreased by 24.8% for males and 21.2% for females on the low sodium‐DASH diet. 27 cases and 14 cases per 10, 000 individuals were prevented for males and females, respectively, in the intervention group. The ICER for the low sodium‐DASH diet strategy was 287, 726 for males and 423, 878 for females compared to the no intervention strategy. Conclusions: Using a Markov model of gastric cancer risk, we found that adherence to a low sodium‐DASH diet could decrease the risk of gastric cancer. This intervention was not cost‐effective due to the high cost of a low sodium‐DASH accordant diet, but significantly improved for high‐risk populations and when the cost of the diet became slightly more affordable. Abstract : Using a Markov model of gastric cancer risk, we found that adherence to a low sodium‐DASH diet decreases the risk of gastric cancer in the U.S. population. This intervention was not cost‐effective due to the high cost of a low sodium‐DASH accordant diet, but significantly improved for certain high‐risk populations and when the cost of the diet became slightly more affordable.